Online Identity Analysis of Public Figure Ketut Permata Juliastrid in Instagram Social Media: Analisis Identitas Daring Tokoh Publik Ketut Permata Juliastrid dalam Media Sosial Instagram - Amiruddin, Muchammad Dicky; Febriana, Poppy (Universitas Muhammadiyah Sidoarjo, 2025)
Technological advancements have driven the popularity of social media, providing many benefits, especially in easy and fast global communication. One of the rapidly growing platforms is Instagram, which is not only used to share photos and videos, but also to express oneself and form an online identity. Public figures such as Ketut Permata Juliastrid, utilize Instagram to build their self-image. This research aims to examine Ketut Permata Juliastrid's online identity formation through managing context collapse and authenticity, and to explore the risks and opportunities related to privacy and surveillance that arise in the use of social media. The study reveals that Tata manages her identity by utilizing personal stories and compelling visuals to build an emotional connection with her followers. However, this also brings challenges in maintaining a balance between public expectations and personal privacy. This research provides insight into the strategies used by public figures in building online identities in the digital age, as well as the challenges faced in protecting their privacy. Highlights: Online Identity & Authenticity – Public figures like Ketut Permata Juliastrid craft their online identity using personal stories and visuals to connect emotionally with followers. Context Collapse Management – Balancing different audience expectations requires careful curation of content to maintain authenticity while managing public perception. Privacy & Surveillance Risks – Sharing personal aspects online poses challenges in protecting privacy and navigating potential surveillance threats. Keywords: Online Identity, Context Collapse, Authenticity, Privacy and Survaillance